Estimation of the infestation rate in coffee berry borer, using a SIR model - Mesa, Mónica J. (2017)
The coffee berry borer, Hypothenemus hampei, is one of the plagues with the highest incidence and affectation in the coffee plantation. Colombia is a region that promotes the growth and infestation of this plague. The infestation is due to several factors such as Colombia’s climate, geographic location and continuous coffee production. Coffee production is one of the most important agricultural activities in the country. Therefore, it is important to carry out studies concerning the dynamics of the coffee borer. For this reason, this article adapts the behavior of the coffee borer with an epidemiological model type SIR proposed by Kermack y Mckendrick. This model and the final size relation (proposed by Castillo Chavez) will be used to estimate the coefficient that represents the infestation of the plague in terms of the other parameters involved in the dynamic. Besides, different numerical simulations were done in Matlab environment by changing the values of the parameters of the dynamic system.